THERMODYNAMIC STUDY OF CADMIUM ADSORPTION ON SYNTHETIC ACTIVATED CARBON FROM IRAQI DATE PIT - ISTABRAQ W. GYAATH (مجلة جامعة الانبار للعلوم الصرفة, 2013)
In this work an activated carbon was prepared from Iraqi dates pit by chemical activation with zinc chloride ( 20%) in present of air the resultant charcoal was54.1 % and the measured of specific surface area was 560.35 m2/mg then studied the adsorption of cadmium at variable concentration on activated carbon and measured the concentration and of cadmium was measured by atomic absorption spectroscopy .studied Langmur and Frendlich equations to find Langmur and Frendlich constants . The results indicated that the adsorption were fitted with Langmur and Frendtich models with highly correlation coefficient and the removal of cadmium by activated carbon from aqueous solutions was more effective process. Mean while the use of Temkim models showed less effective role in cadmium adsorption with low correlation coefficient ( R2=0.71)